The influence of dance on the creativity of elementary school students I- A literature review - Boletini, Tatiana Lima; Barros, Keila Rejane Lopes de; Diniz, Isabel Cristina Vieira Coimbra (Seven Editora, 2024)
The aim of this study was to analyze, through a bibliographical review, the importance of dance in the school context as an instrument to work creativity in the student’s life. This article shows us that through dance, we have the opportunity to learn not only rhythmic models, but also to stimulate and enhance creativity, work on self-confidence, help in the development of critical thinking and in the elaboration of problem solving. It points out the need for the educator to be intentional, stimulating the student in their autonomy, their imagination, providing opportunities for the improvement and development of being creative. It is concluded that developing creative skills has been increasingly required in the current world we live in and dance within the school context, through a pedagogical and intentional look, is extremely important, bringing benefits in terms of enhancing and stimulating the creativity of students. DOI:https://doi.org/10.56238/sevened2024.009-040